Reinvigorating landscapes: using natural environments to enhance quality of life in assisted living facilities - Holzum, Andrew (Kansas State University, 2016)
The senior population within the United States has increased by 1.5% from 2010-2014, whereas other demographics have either stayed the same or have decreased (US Census Bureau, 2014). Assisted living facilities focus on sustaining and enhancing the quality of life for the residents, and their physical and social environments should be modified to stimulate this focus. Studies have shown that is can be accomplished by increasing access to nature. Additionally, a diminished physical activity level among senior citizens is an additional research problem as it contributes to their quality of life. With these research problems in mind, the two research question being addresses are: How does access to nature affect physical activity levels of senior citizens living within assisted living facilities; and how can indoor and outdoor landscapes assist in promoting physical activity? To answer the research questions, the following aims were established in support of the research and design objectives of this study: (1) identify barriers limiting use, and (2) idenify how access to nature affects phyisical activity levels in senior citizens within assisted living facilities, (3) to improve access to nature, (4) to improve quality of outdoor spaces, and (5) to encourage outdoor activity. Research Methods include (a) focus group interviews and (b)an environmental audit to investigate user’s preferences of activities, existing access to nature, and barriers prohibiting the use of the natural environments, (c) literature analysis and research to identify relevant design strategies that have been used in similar studies, and in the design phase,this study synthesizes how design principals can be utilized to solve the identified issues. The findings were then used to create a matrix for design and to also develop design goals and solutions for Homestead. The result of this study identifies strategies used to overcome barriers limiting outdoor use. The focus group and staff interviews along with the environmental audit and the literature analysis findings were used for developing a framework for design. The design framework and research methods this study used could be applied at similar facilities based on the ability ranges of the residents to produce a design solution that encourages outdoor use and physical activity, and thus, enhance the quality of life of the residents in the assisted living facilities.
Keywords: Access to nature; Landscape architecture; Homestead assisted living facility; Assisted living facility; Senior Citizen